Implementasi Sistem Pendukung Keputusan Menggunakan Simple Additive Weighting (SAW) pada Pengadaan Stok Obat - Asrul Azhari Muin; Syahbudin Syahbudin; Herna Febriana (Subaltren Inti Media, 2024)
A medicine is a substance used for diagnosis, pain relief, and for treating or preventing diseases in humans or animals. Medicine in a broad sense is any chemical substance that can affect life processes, so pharmacology is a very broad science. The problem currently faced by Mifta Polewali Mandar Hospital is that all data input and output processes are still done manually, and there is often a shortage or excess of medicines in the pharmacy stockroom during the process of stock procurement, which is an activity to maximise the supply of medicines so that errors do not occur. Errors in stock procurement planning can result in an excess or shortage of medicines. A shortage of medicines can result in less than optimal service to consumers and can affect the pharmacy's profit or revenue. Meanwhile, overstocking results in a lot of expired and wasted medicines because they cannot be returned to the supplier and also requires more space to store medicines. The purpose of this study is to develop a decision support system for drug stock procurement at Mifta Polewali Mandar Hospital and to implement the Simple Additive Weighting (SAW) method in drug stock procurement at Mifta Polewali Mandar Hospital. In this study, the researchers used a type of qualitative research. The results of this study showed that the decision suppo